Pragmatic Language Development: Analysis of Mapping Knowledge Domains on How Infants and Children Become Pragmatically Competent - Ahmed Alduais; Issa Al-Qaderi; Hind Alfadda (MDPI AG, 2022)
New-borns are capable of recognising and producing sounds as they become phonologically competent. Following this, infants develop a system for connecting these sounds, which helps them become increasingly lexically competent over time. Their knowledge of these words grows as they develop, using words to form phrases, turning them into sentences, and ultimately becoming syntactically competent. By making sense of these linguistic elements, these three competencies are enhanced, and this is how infants become semantically competent. As infants continue to develop linguistic and non-linguistic communication behaviours, this miraculous language development becomes even more complex, enabling them to perfect their linguistic abilities while being pragmatically competent. In this study, a scientometric approach was used to examine past, present, and future trends in pragmatic language development (PLD). A total of 6455 documents were analysed from the Scopus, WOS, and Lens databases between 1950 and 2022. The analysis involved the visualisation and tabulation of eight bibliometric and eight scientometric indicators using CiteSpace 5.8.R3 and VOSviewer 1.6.18 software for data analysis. In this study, we highlight the major patterns and topics directing the research on PLD between 1950 and 2022. The themes and topics included (1) analysing PLD as a social behaviour through the lens of executive functions; (2) studying PLD as a social behaviour based on social understanding; (3) examining PLD as a social behaviour associated with autism spectrum disorder; (4) developing an understanding of PLD in academic settings through the examination of executive functions; (5) identifying pragmatic competence versus communicative competence as a social behaviour; (6) analysing pragmatic language skills in aphasic patients via epistemic stances (i.e., attitudes towards knowledge in interaction); (7) investigating PLD as a behavioural problem in the context of a foreign language; (8) assessing PLD as a behavioural problem in individuals with autism spectrum disorder; (9) assessing PLD in persons with traumatic brain injury and closed head injury as a behavioural problem; (10) identifying the role of the right hemisphere in executive functions as a cognitive substrate; (11) assessing the impact of pragmatic failure in speech acts on pragmatic competence; and (12) investigating the patterns of PLD among learning-disabled children.